Making place for Muslims in contemporary India - Menon, Kalyani Devaki (Cornell University Press, 2022)
"This is an ethnography of diverse groups of Muslims in Old Delhi that examines how religion provides an arena to make place for the community, and to challenge exclusionary understandings of nation and belonging in contemporary India"--